Curriculum reform in primary mathematics education: teacher difficulties and dilemmas - AKKOÇ, HATİCE (My University, 2008)
This paper examines primary classroom teachers\" preparedness of implementing a new curriculum model. The new curriculum displays a paradigmatic shift from a behaviourist approach to more of a constructivist one. The development of problem solving skills is particularly emphasised in the new curriculum. Two questionnaires including items on students\" different solution strategies to problems are applied to roughly 500 teachers to seek how teachers value and make sense of different strategies. The data reveals that the teachers are not open to different strategies, have difficulties in evaluating students responses to the open-ended questions and experience serious mathematical difficulties in assessing students\" solutions. We discuss issues raised by the findings with regard to the curriculum implementation.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Bilgisayar ve Öğretim Teknolojisi Eğitimi; Social Sciences and Humanities; Sociology; Education; Computer Education and Instructional Technology; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); EĞİTİM, BİLİMSEL DİSİPLİNLER; Matematik; Temel Bilimler (SCI); EDUCATION & EDUCATIONAL RESEARCH; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); EDUCATION, SCIENTIFIC DISCIPLINES; MATHEMATICS; Natural Sciences (SCI); Genel Sosyal Bilimler; Analiz; Cebir ve Sayı Teorisi; Matematik (çeşitli); Genel Matematik; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Analysis; Algebra and Number Theory; Mathematics (miscellaneous); General Mathematics; Physical Sciences; Social Sciences & Humanities